Ավանդական աղոթքները Ջավախքի ժողովրդական երգարվեստում - Թագակչյան, Զավեն (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Ջավախահայության բնակատեղիներում 20-րդ դարում իրականացված գիտարշավների ժամանակ հավաքված նյութերը փաստում են, որ տեղի ժողովրդական երգարվեստի անկապտելի մասը հանդիսացող հոգևոր աղոթքները բաժանվում են երկու խմբի` 1 հայոց Պատարագամատույցի ժամանակ հնչող երգերի ժողովրդայնացված տարբերակներ, 2 բանասացների հորինած երաժշտախոսքային կառույցներ: В 20-ом веке был организован ряд фольклорных экспедиций в Джавахк – один из девяти регионов Великой Армении, который ныне находится на территории Грузии. Собранный материал свидетельствует о том, что неотъемлемой частью народного песнетворчества джавахкских армян являются священные молитвы, которые можно разделить на две группы: 1. народные варианты песен св. Литургии Армянской Церкви; 2. музыкально-словесное творчество народных сказителей. This research is based on our collection of 20th century field recordings of sacred prayers from the Armenian community of Javakhk. In studying these sacred prayers we demonstrate that they are adaptations of and resemble local folk songs which can be divided into two distinct categories: This research is based on our collection of the 20th century field recordings of sacred prayers from the Armenian community of Javakhk. The results of the study demonstrated that they are adaptations of and resemble the local folk songs which can be divided into two distinct categories: 1. Folk variations of the songs from the Divine Liturgy of the Armenian Apostolic Church 2. Completely new melodic-textual content composed by various informants.
Keywords: Բանահյուսություն